Revision of the Echiniscus bigranulatus group with a description of a new species Echiniscus madonnae (Tardigrada: Heterotardigrada: Echiniscidae) from South America - Michalczyk, Łuka; Kaczmarek, Łukasz (Zootaxa, 2006)
A new species, Echiniscus madonnae sp. nov., is described from moss samples collected in Peru. So far it is the only species within the Echiniscus bigranulatus group that does not have true pores in the dorsal plate cuticle. This paper contains also a redescription of Echiniscus bigranulatus Richters and updated descriptions of Echiniscus ollantaytamboensis Nickel et al. and Echiniscus ranzii Ramazzotti. In this paper we also provide a SEM analysis of the dorsal plate cuticle structure.